2011
DOI: 10.1038/gt.2011.204
|View full text |Cite
|
Sign up to set email alerts
|

Topical application of the antiapoptotic TAT-FNK protein prevents aminoglycoside-induced ototoxicity

Abstract: We previously demonstrated that an artificial protein, TAT-FNK, has antiapoptotic effects against cochlear hair cell (HC) damage caused by ototoxic agents when applied systemically. To examine the feasibility of topical protein therapy for inner ear disorders, we investigated whether gelatin sponge soaked with TAT-FNK and placed on the guinea pig round window membrane (RWM) could deliver the protein to the cochlea and attenuate aminoglycoside (AG)-induced cochlear damage in vivo. First, we found that the immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…The idea is to repair the protein-mediated diseases through the delivery of normal protein in vitro or in vivo. Some strategies have been used to manipulate cell functions by influencing signaling pathways. , For example, we can regulate the biomarkers of p53 and caspase to turn on/off the cell death for the diseases of apoptosis pathways. Delivering antigens to a specific site to stimulate a desired immune response has been explored .…”
Section: Introductionmentioning
confidence: 99%
“…The idea is to repair the protein-mediated diseases through the delivery of normal protein in vitro or in vivo. Some strategies have been used to manipulate cell functions by influencing signaling pathways. , For example, we can regulate the biomarkers of p53 and caspase to turn on/off the cell death for the diseases of apoptosis pathways. Delivering antigens to a specific site to stimulate a desired immune response has been explored .…”
Section: Introductionmentioning
confidence: 99%
“…[17]. Furthermore, Kashio et al reported that an artificial antiapoptotic protein, FNK, mediated with TAT peptide could enter the cochlea and effectively attenuate aminoglycoside-induced apoptosis of cochlear sensory hair cells in a guinea pig model [18]. More recently, Ookubo et al used poly-arginine (R11) to enhance transdermal delivery of several tyrosinase inhibitors on a guinea pig model and found the fusion protein efficiently penetrated through the SC and significantly inhibited UV-induced melanin synthesis [19].…”
Section: Introductionmentioning
confidence: 99%